Development of a family support model to reduce preeclampsia through antenatal care - Indriyani, Diyan; Yunitasari, Esti; Efendi, Ferry (Universitas Airlangga, 2025)
Introduction: One of the pregnancy complications that needs to be monitored is the occurrence of preeclampsia because it has a high risk of maternal and infant death. The risk of preeclampsia during pregnancy can be determined through routine pregnancy checks. Routine pregnancy checks, or antenatal care, have low coverage. This study aimed to investigate the validity of the family centered maternity care (FCMC) construct and the relationship between pregnant women's characteristics, family characteristics, healthcare factors, sources of support, and family support in antenatal visit adherence using structural equation modeling (SEM). Methods: The research design was correlational, using a Cross-Sectional Study approach. A total of 135 respondents were included in this study. The research data were analyzed using structural equation modeling. Results: FCMC-based family support is based on the characteristics of pregnant women, family characteristics, health services, and sources of support, with family characteristics being the most significant contributor to FCMC-based family support. Compliance with antenatal care (ANC) visits is shaped by family characteristics, health services, and FCMC-based family support, where FCMC-based family support is the variable that makes the most significant contribution to ANC visit compliance for pregnant women. Conclusions: Health services are essential for facilitating public health issues, with all efforts and activities carried out to prevent and treat diseases. Health service officers must involve families in antenatal care to avoid complications during pregnancy.